Creative Thinking Skills from 6 to 17 Years as Assessed Through the WCR Test. (2nd June 2015) - Pizzingrilli, Paola; Valenti, Chiara; Cerioli, Luciano; Antonietti, Alessandro
Abstract: Nowadays fostering creativity constitutes an important educational goal, even though teachers notice some difficulties to identify in their students abilities related to the creative thinking. In order to overcome such difficulties teachers should be enabled to apply easy-to-administer tests which allow them to assess students' creativity levels. The purpose of this study was to devise an easy multiple-choice instrument aimed at evaluating the main mechanisms underlying students' creativity. A large sample of students attending Primary and Secondary Schools in South Italy were involved. For each age-level an online test was administered. The test consisted of three sections corresponding to the three mental operations identified by the WCR model (Antonietti and coll., 2011a). The widening process (subtest A) concerns the tendency to generate many ideas. The connecting process (subtest C) refers to the capacity to combine different elements in unusual ways. The reorganizing process (subtest R) consists of changing the perspective and inverting relationships among elements. Results suggested that the test is suitable to evaluate the three mental operations involved in creative thinking. In addition, ANOVAs showed some significant age-level differences in widening, connecting and reorganizing abilities, even though a clear developmental trend failed to emerge. Findings supported the evidence that creativity is multidimensional and that the mental mechanisms involved are affected by age- and context-related variables in different ways.